Octopaminergic system in the central nervous system of the terrestrial slug Limax. Issue 18 (9th June 2016) - Matsuo, Ryota; Tanaka, Marin; Fukata, Rena; Kobayashi, Suguru; Aonuma, Hitoshi; Matsuo, Yuko
ABSTRACT: The terrestrial slug Limax can learn to avoid the odor of some food (e.g., carrot juice) by the simultaneous presentation of an aversive stimulus (e.g., bitterness of quinidine). This type of associative memory critically depends on the higher olfactory center, the procerebrum in the central nervous system. The modulation of the local field potential (LFP) oscillation recorded on the procerebrum has been thought to reflect the information processing of the odor that elicits the behavioral change, such as avoidance of the aversively learned odor or approaching an attractive food's odor. Here we focused on octopamine, an important neuromodulator involved in learning and memory in invertebrates, and considered to be the invertebrate equivalent of noradrenaline. We identified a few octopaminergic neurons in the subesophageal and buccal ganglia, and a larger number near the procerebrum in the cerebral ganglia, using immunohistochmical staining and in situ hybridization of tyramine β‐hydroxylase, an octopamine‐synthesizing enzyme. Application of octopamine reduced the frequency of LFP oscillation in a dose‐dependent manner, and this effect was inhibited by preincubation with phentolamine. High‐performance liquid chromatography analysis revealed the presence of octopamine, noradrenaline, and adrenaline in the central nervous system. Unexpectedly, noradrenaline and adrenaline both accelerated the LFP oscillation, in contrast to octopamine. Our results suggest that octopamine and noradrenaline have distinct functions in olfactory information processing, in spite of their structural similarity. J. Comp. Neurol. 524:3849–3864, 2016. © 2016 Wiley Periodicals, Inc. Abstract : The authors determined the distribution of octopamine‐containing neurons in the CNS of the terrestrial slug Limax, and showed that octopamine reduces the frequency of the local field potential oscillation in the procerebrum, a higher olfactory center of the slug, suggesting the involvement of octopamine in olfactory learning in Limax .